RANCANG BANGUN PENYALURAN JASA ASISTEN RUMAH TANGGA BE8RBASIS WEB PADA PT MANGGA RAYA MAKMUR - Lee, Josh; Saragih, Saut Pintubipar (Universitas Putera Batam, 2024)
Household assistants are a highly sought-after profession in Indonesian society, especially in major cities. However, the process of providing household assistant services still relies on paper documents and excel, which are less efficient and effective. This research aims to design and implement a web-based information system for the distribution of household assistant services at PT. MANGGA RAYA MAKMUR. This information system can help the company manage its business processes online through a website, offering easier, faster, secure, and reliable household assistant service distribution to clients. The research methodology employed in this study is the prototype method, which includes encompassing stages such as building a prototype, prototype evaluation, system coding, system testing, and system evaluation. The information system is designed using the Unified Modeling Language (UML) and built using ReactJS with MySQL as the database. The results of this research indicate that the web-based household assistant service distribution information system can enhance the performance and satisfaction of both the company